Causes of vision impairment and assessment of need for low vision services for students of blind schools in Nepal - Kansakar, I; Thapa, HB; Salma, KC; Ganguly, S; Kandel, RP; Rajasekaran, S (Kathmandu University Medical Journal, 2009)
Background: The present study is first of its kind to evaluate causes of visual impairment of blind students in Nepal and assess their need for low vision rehabilitation services. Aim: To evaluate causes of vision impairment of students enrolled in blind schools in Nepal and assess the need for low vision rehabilitation services in these students. Materials and methods: A survey was conducted in 12 blind schools in Nepal, which were registered with Nepal Association for Welfare of Blindness (NAWB).It was conducted by a team of an ophthalmologist and an optometrist, by using standard eye examination protocols of the World Health Organization Prevention of Blindness Program (WHO/ PBL). Results: Of the 345 students enrolled in 12 schools, 285 students were examined (response rate of 82.61%). The students were in the 5 - 29 years age group. Nearly three-fourth of the children had become blind within one year of age and 52.3% visually impaired at birth and 20.7% developed vision impairment within one year of age. After refraction, 26 students (9.12%) had mild visual impairment, 21 students (7.37%) had severe visual impairment and 238 students (83.51%) were blind. The main cause of vision impairment was found to be corneal 35.79% and retina diseases, mainly dystrophy, 20.35% followed by problems with the whole globe, lens and optic nerve, accounting for 13.33%, 12.63% and 12.98% respectively. The major etiological factors were those of childhood such as Vitamin A deficiency, measles and similar causes (42.11%) followed by hereditary causes (25.26%). Of the total students examined, 48.07% were visually impaired due to preventable causes and 16.14% treatable aggregating to 64.21% of avoidable blindness. Fifty seven (28.22%) students could read smaller than 2 M print size after low vision assessment for near and 33(15.78%) students benefited with telescopic trial for distance low vision. Conclusion: In Nepal, renewed focus on providing best possible quality of life for visually impaired children by proper low vision assessment and eye health education focusing on, general public and community health workers, with governmental and institutional support is required to achieve Vision 2020 objectives to decrease childhood blindness. Key words: childhood blindness, Nepal, blind school study, low vision, vision impairment doi: 10.3126/kumj.v7i1.1764 Kathmandu University Medical Journal (2009), Vol. 7, No. 1, Issue 25, 44-49